Variations in annual winter mean temperature in South China since 1736. (16th October 2015) - Ding, Lingling; Ge, Quansheng; Zheng, Jingyun; Hao, Zhixin
Abstract : Modern meteorological observations in South China from 1960 to 2009 show a strong correlation between winter temperatures and two snowfall parameters, the southern boundary of the snow and the number of snowy days. Based on this relationship, the variation in annual winter mean temperature in South China from 1736 to 2009 was reconstructed using data acquired from Chinese historical documents dating from the Qing dynasty, such as memos and local gazettes. The reconstructed time series were used to analyse variations in winter temperature in South China. Significant interannual and interdecadal changes were found. The maximum temperature difference between neighbouring years was 3.1 °C for 1958–2009 and 3.0 °C for 1736–1957, whereas the maximum temperature difference between adjacent decades was 0.8 °C for the 1960s–2000s and 0.6 °C for the 1740s–1950s. The 2000s was the warmest decade; the mean temperature was 1.6 °C higher than that of the 1870s, which was the coldest decade between the 1740s and the 2000s. The mean winter temperature was warmer in the 18th and 20th centuries and coldest in the 19th century.